Gender difference in extreme cardiac remodelling in endurance Olympic athletes assessed by non-contrast CMR - Maestrini, V.; Birtolo, L. I.; Filomena, D.; Di Giacinto, B.; Squeo, M. R.; Mango, R.; Di Gioia, G.; Lemme, E.; Serdoz, A.; Fallanca, A.; Severino, P.; Gualdi, G.; et al. (European Heart Journal, 2021)
Background: Male and female athletes present difference spectrum of cardiac remodelling related to their sport activity. However data in elite female athletes are scarce and mainly limited to echocardiography evaluation.